Kosmologi Waktu Sembilan Hari Suku Boti di Pulau Timor - Benu, Yebester; Koroh, Lanny Isabela Dwisyahri (Jurnal Lazuardi, 2025)
this research examines the funnction of nine days in the cosmology of the indigenous Boti people in south central Timor,East Nusa Tenggara. In contrast to the modern linear and mechanical view of time,the Boti people view time cyclically with a nine-day cycle called “Neon”. Ths calendar system is the basis for the implementation of customs, traditions and ritulals in their daily lives, which are rooted in the teaching of halaeka as a sacred ancestral belief. Each day in the nine-day cycle has specific meanings and rules governing community activities, such as Neon Ai (fire day), Neon Oe (water day) and Neon Besi (iron day), which reflect the harmonious relationship between humans, nature and supernatural forces. This cosmological view affirms the importance of time as a gift from the Creator that must be honored through active participation, repetition of sacred events, and totality of action. This study confirms that the local wisdom of the Boti Tribe in interpreting time is a unique cultural heritage and needs to be preserved as a source of religious values and cultural identity of indigenous peoples on Timor Island